2018
DOI: 10.3390/ijerph15071311
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health Help-Seeking Behavior among Migrants from Sub-Saharan Africa and South East Asia living in High Income Countries: A Systematic Review

Abstract: The number of migrants has increased globally. This phenomenon has contributed to increasing health problems amongst migrants in high-income countries, including vulnerability for HIV acquisition and other sexual health issues. Adaptation processes in destination countries can present difficulties for migrants to seek help from and gain access to health services. This study examined migrants’ from sub-Saharan Africa (SSA) and South East Asia (SEA) sexual health help-seeking behavior in high-income countries wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 58 publications
3
49
0
Order By: Relevance
“…Epidemiological evidence shows that HIV risk for women is often associated with regular relationships, since interpersonal dynamics in long term relationships may act as a barrier to adopting protective behaviours [51]. Alongside, migration-related stressors including adaptation processes in host countries have been viewed as increasing migrants' vulnerability for sexual health-related problems, such as HIV and other STI [52]. By having condomless sex in both their host country and their homeland, migrants may be at risk of cross-border transmission of HIV and other STI as documented elsewhere [53].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence shows that HIV risk for women is often associated with regular relationships, since interpersonal dynamics in long term relationships may act as a barrier to adopting protective behaviours [51]. Alongside, migration-related stressors including adaptation processes in host countries have been viewed as increasing migrants' vulnerability for sexual health-related problems, such as HIV and other STI [52]. By having condomless sex in both their host country and their homeland, migrants may be at risk of cross-border transmission of HIV and other STI as documented elsewhere [53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has identified the role of community and religious leaders in addressing HIV stigma and increasing uptake of HIV testing [23,71], and peer workers in facilitating access to services [72]. To date, there is little published research on interventions to increase HIV testing among migrants in high-income countries [13,60], and further research is needed to identify what works with different groups in various settings. Interventions should target risks for migrants associated with frequent travel back to countries of birth, promote safe sexual behaviour whilst travelling, and encourage testing on return [26,64].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for late diagnosis of HIV among SSA and SEA migrants living in high-income countries (HIC), such as Australia, are broadly understood. Our previous research indicated that population mobility (movement between countries) can be a risk factor for HIV, as risk behavior of the individual may change in the destination country [8,9,10,11,12,13]. Mobility may also increase vulnerability to HIV acquisition, as an individual’s access to health services and social support changes [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed that more distant healthcare facilities may actually be preferred for stigmatized health conditions (24,25). It is known that migrants perceive more shame and stigma related to STIs (5,26). Also, perceived issues with con dentiality and privacy at the GP may play a role in choosing anonymous STI testing at the SHC (4,27).…”
Section: Discussionmentioning
confidence: 99%